2020
DOI: 10.15171/jlms.2020.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Fractional CO2 Laser on the Quality of Life, General Health, and Genitourinary Symptoms in Postmenopausal Women With Vaginal Atrophy: A Prospective Cohort

Abstract: Introduction: After menopause women experience vaginal atrophy related to hormonal changes and estrogen deficiency. The purpose of this paper was to evaluate the effect of the fractional CO2 laser on the quality of life, vaginal atrophy symptoms, and urine incontinency in menopause women. Methods: This prospective study was conducted among 140 women from 2017 to 2018 in Yas hospital, Tehran University of Medical Sciences. They encountered the fractional microablative CO2 laser system three times at four-week i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 25 publications
(39 reference statements)
4
30
0
Order By: Relevance
“…Previous reviews that assessed randomized controlled trials and observational studies also found evidence suggesting that laser treatment improves vaginal health, vaginal atrophy, and symptoms of urinary incontinence 3,59‐61 . However, it is believed that no previous review has been conducted on studies using radiofrequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reviews that assessed randomized controlled trials and observational studies also found evidence suggesting that laser treatment improves vaginal health, vaginal atrophy, and symptoms of urinary incontinence 3,59‐61 . However, it is believed that no previous review has been conducted on studies using radiofrequency.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, there is a decrease in circulating estrogen, which provokes thinning of the vaginal epithelium and a reduction in its collagen content, hyalinization, and elastin content, thereby increasing the connective tissue density and reducing the vascularity of the vagina. This can lead to burning, fissuring, dyspareunia, and postcoital bleeding 3 …”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, numerous studies have noted significant improvement in GSM, VL, sexual function, and QOL following treatment with vaginal CO 2 laser therapy (Table 1) [20,22,23,38,39,42]. Improvement in urinary incontinence has not been reported with CO 2 laser therapy.…”
Section: Co 2 Lasermentioning
confidence: 96%
“…A more recent prospective cohort study by Reisenauer et al [49] reported that among patients (N=30) receiving two treatments with Er: YAG laser therapy, patients reported a significant improvement in QOL, which had previously not been reported. [38].…”
Section: Erbium:yttrium-aluminum-garnetmentioning
confidence: 99%
“…Intravaginal laser therapy is a new non-pharmacological treatment successfully proposed especially for the management of symptoms produced by menopausal genital atrophy. Due to the satisfactory efficacy of this treatment, the term “vaginal rejuvenation” has been proposed by some authors [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%